Assessing learning styles of undergraduate logistics students using Kolb's learning style inventory: A cross-sectional survey - Mpwanya, M.F.; Dockrat, S. (South African Journal of Higher Education, 2020)
Understanding students’ learning styles and adapting instructional strategies to the variety of student learning styles are determinants for effective learning and enhance learning performance. Using Kolb’s learning style inventory (LSI) and demographic questions, this study assesses the learning styles of undergraduate logistics university students by identifying their dominant learning style and by exploring whether students’ demographic factors influence their learning styles. To this end, a cross-sectional survey involving 429 undergraduate logistics university students in South Africa was conducted. The results show that accommodating learning style as the most predominant learning style among undergraduate logistics university students, followed by students with assimilating learning style. The combined proportion of these two groups of students represents more than two-thirds of the sampled population. The study’s findings show that gender and learning styles were significantly related. While the majority of male logistics students displayed the diverging learning style, their female counterparts exhibited the converging learning style. On the other hand, learning styles and age group; learning styles and type of high school attended; and learning styles and nationality were found not to be related. This study has implications for practice and extends the literature on learning styles and demographic factors in the unexplored logistics discipline.